Combination of generalized-ensemble algorithms and one-dimensional reference interaction site model theory - Mitsutake, A.; Kinoshita, M.; Hirata, F.; Okamoto, Y. (Condensed Matter Physics, 2007)
The article reports an attempt to study the protein folding problem by generalized-ensemble Monte Carlo simulations
with reference interaction site model theory. Generalized-ensemble algorithms greatly enhance the
configurational space sampling in computer simulations. The reference interaction site model theory treats
solvent effects with solvent molecular shape and estimate solvation free energy around proteins. We have
developed simulation algorithms which combine generalized-ensemble algorithms and one-dimensional reference
interaction site model theory. This treatment can also use a simulation with three-dimensional reference
interaction site model theory. In this review, we describe the methods and present the results of these simulations
for a peptide. Стаття присвячена вивченню проблеми згортання протеїну в рамках комбiнацiї узагальненого ансамблю Монте-Карло та теорiї базисної моделi силових центрiв. Алгоритми узагальненого ансамблю можуть ефективно вибирати конфiгурацiйний простiр в комп’ютерних моделюваннях. Теорiя базисних взаємодiючих силових центрiв може враховувати ефекти розчинника в залежностi вiд форми молекул, визначаючи енергiю сольватацiї протеїнiв. Ми розробили комп’ютернi алгоритми, що комбiнують алгоритми узагальненого ансамблю i одновимiрну базисну модель взаємодiючих силових центрiв. Цей пiдхiд може бути також поєднаний з тривимiрною моделлю взаємодiючих силових центрiв. В даному оглядi описуються методи i представлено результати для пептиду.